2021
DOI: 10.1001/jamanetworkopen.2021.21726
|View full text |Cite
|
Sign up to set email alerts
|

Association of Prenatal Exposure to Maternal Drinking and Smoking With the Risk of Stillbirth

Abstract: Key Points Question Is prenatal exposure to maternal drinking and smoking associated with the risk of stillbirth? Findings In this cohort study of 8506 pregnant women (with 11 892 pregnancies) in Cape Town, South Africa, and the Northern Plains in the US, dual exposure to drinking and smoking after the first trimester of pregnancy had 2.78 times the risk of late stillbirth compared with those with no exposure or who had quit before the end of the first trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 26 publications
2
14
2
Order By: Relevance
“…Notwithstanding the evidenced gestational consumption of psychoactive drugs in this examined cohort, no significant correlations were found between neonatal outcomes, mothers’ hair results, and interview answers. This is in contrast with previous studies showing a correlation between gestational consumption of tobacco and drugs of abuse and increased risk of spontaneous abortions, reduction in neonatal birth weight and birth length, newborn head circumference, and signs of a more severe neonatal abstinence syndrome [ 27 , 35 , 36 , 37 , 38 ]. It can be hypothesized that in this examined cohort, psychoactive drugs consumption during pregnancy was sporadic and, even if identifiable by hair testing, did not affect offspring features.…”
Section: Discussioncontrasting
confidence: 99%
“…Notwithstanding the evidenced gestational consumption of psychoactive drugs in this examined cohort, no significant correlations were found between neonatal outcomes, mothers’ hair results, and interview answers. This is in contrast with previous studies showing a correlation between gestational consumption of tobacco and drugs of abuse and increased risk of spontaneous abortions, reduction in neonatal birth weight and birth length, newborn head circumference, and signs of a more severe neonatal abstinence syndrome [ 27 , 35 , 36 , 37 , 38 ]. It can be hypothesized that in this examined cohort, psychoactive drugs consumption during pregnancy was sporadic and, even if identifiable by hair testing, did not affect offspring features.…”
Section: Discussioncontrasting
confidence: 99%
“…Women exposed to tobacco during pregnancy had a higher odds of alcohol consumption among our study participants. This double exposure to tobacco and alcohol increases the risk of stillbirth [48], sudden infant death syndrome (an important cause of post-neonatal mortality) [49] and other adverse outcomes more than each substance alone [50]. Additionally, we found that a history of induced abortion increased the likelihood of CEATU by fivefold compared with women without a similar history.…”
Section: Discussionmentioning
confidence: 91%
“…A pregnancy loss or fetal death before 20 weeks, according to the US definition for the SPS, was defined as a miscarriage, whereas a non-live birth at ≥20 weeks was regarded as a stillbirth. [ 31 33 ] Terminations of pregnancies after 20 weeks were done for medical reasons. Death of a liveborn infant before the age of 1 year was defined as an infant death.…”
Section: Methodsmentioning
confidence: 99%